A non-dissociative open-flask hydroboration with ammonia borane: ready synthesis of ammonia–trialkylboranes and aminodialkylboranes. Issue 80 (2nd September 2016) - Ramachandran, P. Veeraraghavan; Drolet, Michael P.; Kulkarni, Ameya S.
Abstract : A convenient open-air hydroboration of olefins using ammonia borane in refluxing tetrahydrofuran via an unprecedented non-dissociative mode is described. Abstract : Under open-flask conditions, ammonia borane hydroborates olefins in refluxing tetrahydrofuran. Unlike conventional hydroboration, the Lewis base (ammonia) is not dissociated from the boron center. Terminal alkenes selectively provide ammonia–trialkylborane complexes. On the other hand, internal alkenes afford aminodialkylboranes via a metal-free hydroboration–dehydrogenation sequence. Alkaline hydrogen peroxide oxidation of the products provides the corresponding alcohols in high yields.